Firefighting Vehicles Braking Distance Metering - Izabela Sudrychova; Jiri Kuczaj; Ladislav Janosik; Pavel Polednak; Ivana Janosikova (Communications - Scientific letters of the University of Zilina, 2019)
The paper topic is concerned with the issue of braking dynamics and adhesion coefficients of firefighting vehicles at fire rescue units. The real breaking distances at firefighting vehicles of the water tenders type are presented in the paper. The metering was made on the wet and/or dry asphalt, with different age of tires and the carload. Measured results should be used for drivers’ education at fire rescue units to increase the safety during the emergency drives.